2008
DOI: 10.1501/sporm_0000000130
|View full text |Cite
|
Sign up to set email alerts
|

Puberte Öncesi̇ Dönemde Denge Ve Esnekli̇ği̇n Çevi̇kli̇k Üzeri̇ne Etki̇leri̇ni̇n İncelenmesi̇

Abstract: ÖZETBu araştırmada; puberte öncesi dönemi çocuklarda, denge ve esnekliğin çeviklik üzerine etkilerini belirlemek amaçlandı. Araştırma; yaş ortalamaları 11.12±0.96 yıl olan, 35 (20 erkek, 15 kız) kişilik bir grup üzerinde yürütüldü. Grubun, boy uzunluğu ve vücut ağırlığı ölçümleri yapılarak, beden kitle indeksi değerleri hesaplandı. Çalışmaya gönüllü olarak katılan araştırma grubuna, denge (flamingo) ve esneklik (otur-Uzan) testleri ile birlikte çeviklik testi (illinois) uygulandı.Araştırmadan elde edilen veril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
13

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 5 publications
(5 reference statements)
0
8
0
13
Order By: Relevance
“…Similarly, in another study, it was observed that improvement of balance skill was done through psychomotor trainings and correlated with the motor skills like walking, running, jumping, climbing, acceleration, etc. (Hazar & Taşmektepligil, 2008;Psychomotor development, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in another study, it was observed that improvement of balance skill was done through psychomotor trainings and correlated with the motor skills like walking, running, jumping, climbing, acceleration, etc. (Hazar & Taşmektepligil, 2008;Psychomotor development, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that performing various and complex actions simultaneously or successively affects reaction and action time positively by enabling individuals to feel mentally alert. Thus, individuals change their direction and speed more quickly (Bompa & Haff, 2015;Hazar & Taşmektepligil, 2008). It was observed that circuit training constituted with repetitive take off, climbing, running, push off and pull was effective in motor development (Bompa & Haff, 2015;Günay, Tamer, & Cicioğlu, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…He used the other arm to balance. The number of trials of participants who succeeded in maintaining the balance for 1 minute was calculated and measured [10].…”
Section: Flamingo Balance Testmentioning
confidence: 99%
“…The extreme point at which the fingers extend is measured in cm. Athletics and gymnastics groups repeated this three times and the best grade achieved was recorded [10].…”
Section: Flexibility (Sit and Reach Test-out)mentioning
confidence: 99%
“…Denge; statik denge ve di-namik denge olmak üzere ikiye ayrılarak da incelenebilir. Statik denge; vücudun dengesini belli bir yerde ya da pozisyonda sağlama yeteneği iken, dinamik denge; hareket ederken vücudun dengesini sağlama yeteneğidir (Hazar ve Taşmektepligil, 2008). Dengenin kontrolü, duyusal girdilerin bütünleşmesi yanında esnek hareket şekillerinin planlanması ve uygulanmasını içeren kompleks bir motor yetenektir (Ferdjallah, Harris, Smith ve Wertsch, 2002).…”
Section: Introductionunclassified